PERBANDINGANEFEKPEMBERIANAIR KELAPA MUDADAN AIR PUTIHTERHADAPKECEPATANPEMULIHAN DENYUT NADIPADA PEMAIN FUTSAL FK UNRAM - Widiastuti, Ida Ayu Eka; Wiguna, Putu Aditya (Jurnal Kedokteran, 2013)
In physical activities, oxygen consumption, heart rate, body temperature and chemical compound in human body will alter transformation. Indirect method to measure workload can be done by measuring pulse during activities. Fluid loss in activities can be replaced by administering fluid that have good rehydration effect, among those are coconut water and drinking water. The aim of this study is to compare the effect of coconut water and drinking water consumption on pulse recovery time after exercise. This experimental study was conducted with randomized pre and posttest group design. Subject of this study is Mataram University Faculty of Medicine futsal team. Fourteen subjects were divided into two groups, each group consist of seven individuals. Coconut water was given to group 1 and drinking water was given to group 2 after treadmill exercise using Bruce Protocol for 15 minutes. The data were analyzed by using MannWhitney Test. Pulse recovery time average of group 1 that consumes coconut water was 157, 29 seconds or 2 minutes 62 seconds, while group 2 that consumes drinking water average was 282,86 seconds or 4 minutes 71 seconds. Mann-Whitney analysis shows that pulse recovery times after treadmill exercise were not significantly different (p > 0.05).Pulse recovery time average on group that consumed coconut water were better (28.5%) than group that consumed drinking water, but were not significantly different (p > 0.05). Keywords :Treadmill exercise, recovery time, coconut water, drinking water, futsal player